Working with trans survivors of sexual violence : a guide for professionals - Rymer, Sally; Cartei, Valentina (Jessica Kingsley Publishers, 2019)
This book provides practical advice for professionals working with transgender (including non-binary) people who have survived any form of sexual violence or abuse. It gives professionals an understanding of the impact and trauma of sexual violence on trans people, as well as the additional difficulties they face accessing services that have traditionally been designed to serve cisgendered clients. The authors reveal specific issues faced by trans people as they recover from traumatic sexual experiences, and what steps professionals and organisations can take to meet the needs of the trans community. They also take a critical look at what can be done to reduce discrimination and how to mitigate the traumatic effects of sexual violence on trans individuals, by recommending effective responses to all levels of service delivery, from organisational policies to advice for front-line professionals.